Letters from pharmacy preceptors : pearls for success - Raub, Joshua N.; Walker, Cathy L.; White, Sara J., 1945- (American Society of Health-System Pharmacists, 2019)
"The Work will be led by Co-Editors Joshua Raub, Sara J. White, and Cathy Walker. It will be comprised of 22 letters from successful pharmacy preceptors in various types of practice roles and organizations. Contributors would be drawn from various aspects of health-system pharmacy practice (clinical, informatics, leadership, ambulatory, etc.) as well as academia, corporate, and federal service, etc., and include winners of the ASHP Residency Excellence award that recognizes the achievements of residency programs and practitioners who have demonstrated excellence and leadership in the training of pharmacy residents. In addition to reflecting on their experiences, the contributors will be asked to share what has inspired them to be preceptors and the rewards of service to learners"--